2019
DOI: 10.1186/s41936-019-0113-3
|View full text |Cite
|
Sign up to set email alerts
|

Farmers knowledge, perceptions and management of Kersting’s groundnut (Macrotyloma geocarpum Harms) insect pests in Benin

Abstract: Background: Macrotyloma geocarpum Harms is a neglected and underutilized crop in Benin subject to several constraints including storage insect attacks, which contribute to the decrease in its production. An ethnobotanical survey using a semi-structured questionnaire was conducted in 15 villages in southern and central Benin to document farmers' perceptions of M. geocarpum storage insect pests and their traditional management practices. Results: The results showed that insect pest were the most important storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Consequently, some management practices should be implemented by the government and farmers, including developing a protocol for visual inspection of RPW infestation; establishing a quick, reliable, cost-effective, and easily applicable early detection device or technique for RPW infestation; and conducting a risk assessment of the area using both visual observation and pheromone traps [25]. This result is aligned with other studies [20,30,53,54] that have reported a positive relationship between knowledge of symptoms and IPM adoption for various pests.…”
Section: Discussionsupporting
confidence: 74%
“…Consequently, some management practices should be implemented by the government and farmers, including developing a protocol for visual inspection of RPW infestation; establishing a quick, reliable, cost-effective, and easily applicable early detection device or technique for RPW infestation; and conducting a risk assessment of the area using both visual observation and pheromone traps [25]. This result is aligned with other studies [20,30,53,54] that have reported a positive relationship between knowledge of symptoms and IPM adoption for various pests.…”
Section: Discussionsupporting
confidence: 74%
“…An integrated and effective approach to controlling pests requires good technical awareness and knowledge which necessitates continuous monitoring, thus rendering the approach more expensive with multiple indirect costs, unlike the plain usage of pesticides. Therefore, technical awareness and advocacy aimed at promoting CS-IPM innovations and the concept at large is indispensable and can only be achieved through an effective knowledge transfer process [32,65]. For example, deficiencies in knowledge have been found to be key impediments to innovation uptake among Ghana's farming households [29].…”
Section: Knowledge On Cs-ipm Practicesmentioning
confidence: 99%
“…For example, deficiencies in knowledge have been found to be key impediments to innovation uptake among Ghana's farming households [29]. Unfortunately, most farm households in Africa either lack proper access to knowledge or sometimes are unable to utilize effectively existing knowledge [65]. Moreover, successful and useful adaptation to innovations necessitates the need to have sufficient knowledge about existing alternatives of the innovations to be adapted, the technical ability to evaluate these alternatives, and subsequently the technical capability to select contextually suitable alternatives for implementation [66,67].…”
Section: Knowledge On Cs-ipm Practicesmentioning
confidence: 99%
“…Tey provide essential proteins, vitamins, and dietary fber for consumers. Kersting's groundnut is an important African indigenous leguminous crop grown on a small scale in West Africa [5]. It originated in West Africa and is widely consumed in Benin, Burkina Faso, Ghana, Mali, Niger, Nigeria, and Togo [6].…”
Section: Introductionmentioning
confidence: 99%